The Antibacterial Activity of Amber Honey and White Honey on Pseudomonas aeruginosa Multi Resistant (PaMR) and Methicillin Resistant Staphylococcus aureus (MRSA) - Faisal Yusuf Ashari; Setio Harsono; Manik Retno Wahyunitisari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Infection of burn wound is a chronical disturbance to the skin, which is caused by Staphylococcus aureus and Pseudomonas aeruginosa, but lately many cases found that both bacteria have been resistant to the antibiotic. To overcome the infection caused by those bacteria, it is important to search for natural substance that has antibacterial activity to both bacteria. The power of natural substance is underestimated. Studies reveal that honey can be more effective for healing burns than modern medicine. The previous research revealed that amber honey and white honey were used as an alternative treatment against Pseudomonas aeruginosa Multi Resistant (PaMR) and Methicillin Resistant Staphylococcus aureus (MRSA). The aim of this study was to evaluate the antibacterial activity of amber honey and white honey on PaMR and MRSA.Methods: This research was conducted by performing antibacterial test phase, determining Minimum Inhibitory Concentration (MIC), and determining comparison value of antibacterial activity from amber honey and white honey to tetracycline.Results: The result of this research showed that both amber honey and white honey have antibacterial activity to both bacteria, by way of stronger antibacterial activity from white honey than amber honey. Amber honey and white honey have the same PaMR activity. MIC of white honey was 7.1% (to MRSA) and 12.3% (to PaMR), while MIC of amber honey was 10% (to MRSA) and 12.5% (to PaMR). The comparison value of antibacterial activity between amber honey and white honey to tetracycline for MRSA was equal to 1:1.08 x 10-4 and 1:1.62 x 10-4. The comparison value of antibacterial activity between amber honey and white honey to tetracycline for PaMR was equal to 1:5.62 x 10-6 and 1:1.03 x 10-5 .Conclusion: Amber honey and white honey have antibacterial activity against MRSA and PaMR.